Deformation Behaviours in Alloy 718 And Medium-high Entropy Alloys - Joy, John (My University, 2023)
The present study focuses on investigating the intermediate temperature embrittlement (ITE) behaviour of the nickel-based superalloy 718 under various strain rates and heat treatment conditions. Tensile tests were performed at room temperature, 650℃, and 750℃ with strain rates ranging from 10!", 10!#, 10!$ & 10!%s!". The tensile strength and elongation were compared across different test conditions. Loss of ductility or intermediate temperature embrittlement phenomena were observed at 650℃ and 750℃ under low strain rates of 10!$ & 10!%𝑠!" and elongation is improved upon high strain rate. To investigate the underlying mechanisms, advanced microstructural analysis was conducted to identify influence of temperature and strain rate dependent mechanism at grain boundary and matrix. Advanced techniques such as Field Emission Gun Scanning Electron Microscopy with Energy Dispersive Spectroscopy, Electron Backscatter Diffraction, and Electron Channelling Contrast Imaging were employed for detailed microstructure characterization. The results show that the presence of Laves phase, DSA and oxidation assisted intergranular cracks may promote ITE. On the other hand, ITE in Alloy 718 can be avoided with a higher strain rate.
Keywords: Intermediate temperature embrittlement; Nickel based super alloys; IN718; Tensile test; Deformation; precipitation; SEM; EBSD; ECCI; Thermo-calc